1980
DOI: 10.1210/jcem-51-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Hormones in Aging Men. I. Measurement of Sex Steroids, Basal Luteinizing Hormone, and Leydig Cell Response to Human Chorionic Gonadotropin

Abstract: Although alterations of circulating sex steroids have been reported in aging men, it is not known to what extent reported changes may represent effects of variables other than aging. We have measured sex hormone levels, serum binding, the testosterone (T) response to hCG, and basal LH levels in 69 male volunteers, aged 25-89 yr, without alcoholism, obesity, chronic illness, or severe prostatic disease, and not using potentially interfering medications. In our study there was no effect of age on serum T, 5 alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
3
9

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(123 citation statements)
references
References 36 publications
10
101
3
9
Order By: Relevance
“…7 Furthermore, there is a significant elevation of E 2 level in these individuals. 8 Similar pathophysiological imbalance between androgen and oestrogen is likely to be associated with other clinical states of adult-onset hypogonadism 9 as well as hyperoestrogenism.…”
Section: Introductionmentioning
confidence: 92%
“…7 Furthermore, there is a significant elevation of E 2 level in these individuals. 8 Similar pathophysiological imbalance between androgen and oestrogen is likely to be associated with other clinical states of adult-onset hypogonadism 9 as well as hyperoestrogenism.…”
Section: Introductionmentioning
confidence: 92%
“…As early as 50-60 years ago it was realized that aging is accompanied by significant reduction in testosterone levels [97,98]. Although some follow-up studies failed to detect age-related decline in plasma testosterone levels in older men [99][100][101][102][103][104], subsequent population-based cross-sectional and longitudinal studies have confirmed progressive loss of testosterone with aging in healthy men [96,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Mirroring this decline in plasma testosterone concentration is an age associated increase in sex-hormonebinding globulin (SHBG) level [117], a major plasma carrier of testosterone, resulting in even more dramatic decreases in unbound free testosterone [110,[123][124][125], and weakly bound bioavailable testosterone [126,127].…”
Section: Humansmentioning
confidence: 99%
“…In contrast to these findings, Sniffen, [139], as well as Sokal [140] observed no loss of Leydig cells with age, while Kothari and Gupta [141] reported total Leydig cell mass to be increased in testes from their older men. Besides, a number of studies have also shown impaired testicular responsiveness to hCG stimulation [103,104,133,[143][144][145][146] or to recombinant human LH [147,148] stimulation in aging men. Harman and Tsitouras [103], Nieschlag et al, [104], Rubens et al, [144], Nieschlag et al, [142], and Nankin et al, [146] all noted decreases in both the absolute and relative (i.e., ratio of stimulated to basal) testosterone responsiveness in elderly as compared to young men.…”
Section: Humansmentioning
confidence: 99%
“…(Zumoff et al, 1982;Bremner et al, 1983). However, others suggest that there is no decline in testosterone with age (Harman & Tsitouras 1980), but this may have been due to afternoon sampling, and patient selection bias as Bremner et al (1983) clearly showed a loss of the early morning rise in testosterone and lower mean testosterone levels over 24 h.…”
Section: Ageingmentioning
confidence: 99%